Recent advancements in the role of phytochemicals and medicinal plants in prophylaxis and management of Alzheimer’s disease - Mishra A.; Krishnamurthy S. (My University, 2025)
Medicinal plants and phytochemicals are some of the major sources in the treatment of various neurodegenerative disorders including Alzheimer’s disease (AD). There is no FDA-approved drug to target AD pathology directly. Full cognitive restoration and management of psychosis-like symptoms are still to be achieved. Being comparatively safer with fewer side effects, medicinal plants have been among the major areas of interest to be researched. Several mechanistic pathways are involved in AD including anticholinesterase activity, glutamate toxicity, free radicals generation, Amyloid β (Aβ) toxicity, inflammation, and mitochondrial dysfunction. Various phytochemicals such as paenol, andrographolide, isoquercitrin, flavonoids, and saponins obtained from different plant sources, various medicinal plants like Spirulina maxima, Salicornia europaea, Curcuma longa, Citrus Junos Tanaka, Cassiae semen, Centella asiatica as well as various traditional medicinal plants of China, Asia, Europe, Turkey, and Iran have been found effective against one or more of these targets. Large numbers of clinical trials are under process to evaluate the role of different phytoconstituents in AD management. Out of 143 agents under clinical trials, 119 have been categorized as disease-modifying agents. The present review extensively covers the recent advancements in the usage of phytochemicals and medicinal plants in various experimental AD models. It involves clinical trials and other research works divided into three sections, including those performed in vitro, in vivo, and in humans mainly from the last five years along with disease markers and mechanistic pathways involved. However, phytochemicals should be explored further in order to achieve neurorestoration in AD. © 2024 mums.ac.ir All rights reserved.